Trocando as lentes: um olhar sobre mulheres e homens que procuram a Justiça para entregar uma criança para adoção. - Souza, Ana Claudia Oliveira de Lima (2019)
The child cession and abandonment are part of the western society history, however, takes on, in each historical moment, different meanings, motivations and distinct social impacts. Currently, the child cession for adoption by his birth mother became object of constant standardization, for example the law nº 12.010/2009, which changed the Estatuto da Criança e do Adolescente/ Child and Adolescent Statute aiming to assure to the women the right of not exercising the maternity, and to the children, the possibility of having preserved his right to family and community life. Since then, the services that welcome women who express an intention to give away their child for adoption has been increasing in the Childhood’s Courts of our country. In 2009, Recife’s Childhood and Youth Second Court began to listen women who expressed their interest give away their child for adoption, through the Program “Mãe Legal”. During these years, it has been verified that, sometimes, it is the parents, as a couple, who appear to express the intention to donate the child for adoption. Therefore, the general objective of this research was to understand the motivations that lead the parents to decide on the cession or recoil from putting a child for adoption, within the Program “Mãe Legal”. Specifically, it has intended to: analyze the process by which the parents experience the parenthood; understand the context lived by the couple that influenced their decision and know familiar aspects that may have influenced the cession or withdrawal of placement of a child for adoption. The research had a qualitative nature and had as an instrument the analysis of documents that were part of the judicial process. Were found 18 cases between October 2009 and December 2017. Of these, five cases were selected for the study. The data were analyzed through the analysis of thematic content. The main results pointed that in addition to the subjective issues, which have their degree of importance, most of the motivations find their roots in external factors, such as: the context in which the couple is living; lack of family support; violence and weariness of conjugality; the interruption of planned dreams; lack of pregnancy planning; unemployment and financial difficulties. We understand that the problematic demands a global comprehension of the phenomenon and that the right to give away a child for adoption is lawful and has to be enjoyed with the greatest degree of autonomy possible. Thus, we consider that the research on this thematic is of great relevance and new studies are made urgent to suggest ways for professionals of the Judiciary, of the health network and of social assistance, in the exercise of the reception and formulation of public policies on the subject.